2018
DOI: 10.1016/j.scitotenv.2017.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Assessing urban population vulnerability and environmental risks across an urban area during heatwaves – Implications for health protection

Abstract: Heatwaves can lead to a range of adverse impacts including increased risk of illness and mortality; the heatwave in August 2003 has been associated with ~70,000 deaths across Europe. Due to climate change, heatwaves are likely to become more intense, more frequent and last longer in the future. A number of factors may influence risks associated with heat exposure, such as population age, housing type, and location within the Urban Heat Island, and such factors may not be evenly distributed spatially across a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(81 citation statements)
references
References 51 publications
2
76
0
3
Order By: Relevance
“…We do not include local variations in outdoor temperature from Urban Heat Island effects in the model due to the lack of spatial information in the EHS, however previous studies have estimated that the UHI leads to an increase of 21-50% in heat-related mortality during hot weather in the West Midlands [15,25]. We therefore assumed that all dwelling variants and occupant age groups have equivalent exposures to elevated UHI temperatures, which may not be the case [19]. Modelled dwelling adaptations, such as white roofs, may themselves affect the UHI.…”
Section: Discussionmentioning
confidence: 99%
“…We do not include local variations in outdoor temperature from Urban Heat Island effects in the model due to the lack of spatial information in the EHS, however previous studies have estimated that the UHI leads to an increase of 21-50% in heat-related mortality during hot weather in the West Midlands [15,25]. We therefore assumed that all dwelling variants and occupant age groups have equivalent exposures to elevated UHI temperatures, which may not be the case [19]. Modelled dwelling adaptations, such as white roofs, may themselves affect the UHI.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to urban street trees, an ecological analysis controlling for indices of area level greenspace, income, deprivation, and smoking rates, showed that London boroughs with higher densities of street trees had lower anti-depressant prescription rates ( [100]; see [105] for similar findings in the US). A review of the urban tree literature reported a range of other potential benefits to health, such as reduced particulate air pollution, plus some challenges such as increased exposure to pollen [10].…”
Section: Benefits Of Natural Environmentsmentioning
confidence: 98%
“…It has been shown previously that there is a strong relationship between air temperature and the health of both humans and the ecosystem [36][37][38]. Heat waves, which are caused by continuous extreme weather, are one of the most important factors in this relationship [39,40]. Long-term exposure to high temperature will greatly increase mortality.…”
Section: Evaluation Criteria Of Urban Heat Environment Riskmentioning
confidence: 99%
“…Long-term exposure to high temperature will greatly increase mortality. Although, these above studies commonly defined the relationship of health with air temperature, there are a number of studies showing that there is high agreement between increased levels of LST and air temperature [39][40][41]. Therefore, this paper uses LST levels in summer to define the urban heat environment risk.…”
Section: Evaluation Criteria Of Urban Heat Environment Riskmentioning
confidence: 99%